IMPLEMENTATION OF HEALTH-BASED STANDARD OPERATING PROCEDURES (SOP) AS COVID-19 MITIGATION IN HOTEL INDUSTRY - Anita Wijayanti; Kartika Hendra Titisari; Purnama Siddi; Riana Rachmawati Dewi (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2021)
In Indonesia, the Covid-19 virus has infected since March 2, 2020. Since then, the Large-Scale Social Restrictions (PSBB) policy has been implemented in several areas with a high spread of the virus, (Regulation of the Minister of Health of the Republic of Indonesia No. 9 of 2020). This is used to suppress the spread of the virus. Hospitality is one of the tourism industries affected. The problem of hotel occupancy rates has decreased due to the Covid 19 pandemic in hotels, forcing a number of hotels to experience temporary or permanent closures. In an effort to develop standard governance standards in mitigating the impact of the Covid 19 outbreak for the hotel industry, the community service team views the need to establish standard operating procedures (SOPs) to prevent and control the impact of Covid 19 in the hotel industry. The object of this activity is the management of Hotel Laweyan Surakarta. The methods used were socialization, FGD and trials. At this stage the output produced is SOP Front Office and Housekeeping. The PKM team also helped with a set of tools for washing hands and personal protective equipment. SOPs are important especially for disaster mitigation and health services to control the stages of activities so that they are easy to monitor.